Perancangan Aplikasi Sistem Informasi Akuntansi Persediaan Menggunakan Microsoft Access 2016: (Studi pada UMKM Seblak Lada Hitam Teh Rindu) - Baihaqi, Fawwaz Al; Supriatna, Iyeh; Surya, Rendra Trisyanto (Indonesian Accounting Literacy Journal, 2025)
Human development will certainly be followed by the development of increasingly sophisticated technology, computer technology is a tool that greatly helps humans to make work more effective and efficient. So the inventory accounting information system is very important in the development of a business. By still using a manual recording system for its company, UMKM Seblak Lada Hitam Teh Rindu, it has resulted in several problems such as the absence of evidence of reports related to inventory and the existence of unrecorded inventory. In this study, the author aims to design an inventory accounting information system application using Microsoft Access 2016 using the SDLC (System Development Life Cycle) design method. This application aims to help companies to be able to record and make reports related to warehouse inventory owned by the related UMKM